Starting point for benchmarking outcomes and reporting of pituitary adenoma surgery within the European Reference Network on Rare Endocrine Conditions (Endo-ERN): results from a meta-analysis and survey study - Zamanipoor Najafabadi, Amir H; van der Meulen, Merel; Priego Zurita, Ana Luisa; Faisal Ahmed, S; van Furth, Wouter R; Charmandari, Evangelia; Hiort, Olaf; Pereira, Alberto M; Dattani, Mehul; Vitali, Diana; de Graaf, Johan P; Biermasz, Nienke R; et al. (Endocrine connections, 2023)
OBJECTIVE: The European Reference Network on Rare Endocrine Conditions (Endo-ERN) aims to organize high-quality healthcare throughout Europe, including care for pituitary adenoma patients. As surgery is the mainstay of treatment, we aimed to describe the current surgical practice and published surgical outcomes of pituitary adenoma within Endo-ERN. DESIGN AND METHODS: Systematic review and meta-analysis of studies reporting surgical outcomes of pituitary adenoma patients within Endo-ERN MTG6 pituitary reference centers between 2010 and 2019. A survey was completed by reference centers on their current surgical practice. RESULTS: A total of 18 out of 43 (42%) reference centers located in 7 of the 20 (35%) MTG6-represented countries published 48 articles. Remission rates were 50% (95% CI: 42-59) for patients with acromegaly, 68% (95% CI: 60-75) for Cushing's disease, and 53% (95% CI: 39-66%) for prolactinoma. Gross total resection was achieved in 49% (95% CI: 37-61%) of patients and visual improvement in 78% (95% CI: 68-87). Mortality, hemorrhage, and carotid injury occurred in less than 1% of patients. New-onset hypopituitarism occurred in 16% (95% CI: 11-23), transient diabetes insipidus in 12% (95% CI: 6-21), permanent diabetes insipidus in 4% (95% CI: 3-6), syndrome of inappropriate secretion of antidiuretic hormone (SIADH) in 9% (95% CI: 5-14), severe epistaxis in 2% (95% CI: 0-4), and cerebrospinal fluid leak in 4% (95% CI: 2-6). Thirty-five (81%) centers completed the survey: 54% were operated endoscopically and 57% were together with an ENT surgeon. CONCLUSION: The results of this study could be used as a first benchmark for the outcomes of pituitary adenoma surgery within Endo-ERN. However, the heterogeneity between studies in the reporting of outcomes hampers comparability and warrants outcome collection through registries.
Keywords: surgery; pituitary; registry; Endo-ERN